BRAIN ABSCESS DUE TO Staphylococcus aureus OF CRYPTOGENIC SOURCE IN AN HIV-1 INFECTED PATIENT IN USE OF ANTIRETROVIRAL THERAPY - Anna Paula Romero de OLIVEIRA; Mara Cristina PAPPALARDO; Daniel DANTAS; Diogo LINS; José Ernesto VIDAL (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
The spectrum of neurological complications associated with human immunodeficiency virus type 1 (HIV-1) infection is broad. The most frequent etiologies include primary diseases (caused by HIV itself) or secondary diseases (opportunistic infections or neoplasms). Despite these conditions, HIV-infected patients are susceptible to other infections observed in patients without HIV infection. Here we report a rare case of a brain abscess caused by Staphylococcus aureus in an HIV-infected patient. After drainage of the abscess and treatment with oxacilin, the patient had a favorable outcome. This case reinforces the importance of a timely neurosurgical procedure that supported adequate management of an unusual cause of expansive brain lesions in HIV-1 infected patients.